Many-to-Many - Field Guide with learnings, models, insights and tools - Zucker, Michelle; Dhami., Annette (Dark Matter Lab, 2025)
A living library of practical tools, frameworks, and case studies desi gned to support practitioners in complex collaborations. Many-to-Many System -aims to support collaborations tackling complex, entangled cha llenges where disrupting norms and values, ownership, and power is ess ential. Solving today’s complex, interconnected problems requires what we term “complex collaborations” - bringing together many diverse gro ups (public, private, civic) with many new perspectives, including fut ure generations and the natural world. While many collaborations are a lready doing great work, we believe that finding better ways to suppor t how they are structured and organised them could unlock more effecti ve, system-level change. The Many-to-Many System is focussed on unlock ing the governance, organising, legal, and learning structures of comp lex collaborations to enable many resources, not just money, but also knowledge and relationships to flow more freely, and to foster many wa ys of working that embrace diverse value exchange. For each and everyo ne of us, our fundamental understandings of the world are influenced b y ‘deep codes,’ often invisibly embedded within our creations, framewo rks, and rules. The Many-to-Many System explored how these codes shape collaboration and governance, aiming to understand if they could be r eimagined and how those within complex collaborators themselves can em bed them into their collaboration’s infrastructures. More intentional and visible shifting of deep codes for governance and organising could help collaborations to better align with their systemic missions and offer approaches for rethinking core concepts like value, power, risk, and ownership. The Many-to-Many System distills two years of learning , prototyping, research, and practice. Here we offer a blend of elemen ts: a core framework, practical insights and learnings, illustrative m odels for complex topics, and tools developed along the way. Our aspir ation is to provide a range of resources that can help others embed th e Many-to-Many deep code shifts into their own complex collaboration w ork.